Anterior-posterior systematic deficits of cortical thickness in early-onset schizophrenia - Yun-Shuang Fan; Yong Xu; Bin Wan; Wei Sheng; Chong Wang; Mi Yang; Sofie Louise Valk; Huafu Chen (Communications Biology)
Abstract Schizophrenia is a neurodevelopmental condition with alterations in both sensory and association cortical areas. These alterations have been reported to follow structural connectivity patterning, and to occur in a system-level fashion. Here we investigated whether pathological alterations of schizophrenia originate from an early disruption of cortical organization. We found a structural covariance gradient axis of cortical thickness discriminated anterior from posterior region and was compressed in early-onset schizophrenia (EOS) patients. Patients showed increased structural covariance between two ends of the anterior-posterior axis, with increased geodesic distance of covarying regions between two ends. Positive symptoms increased with the strengthening of structural covariance between two ends. Our findings revealed a contracted organizational axis in EOS patients, which was attributed to excessive distally coordinated changes between anterior and posterior cortical regions. Our study from a systematic perspective suggests disturbed maturational processes of cortical thickness in EOS, supporting the neurodevelopmental hypothesis of schizophrenia.